Non-cardiac surgery following drug-eluting coronary stent implantation—a question of timing? - Mitchell, Andrew J.; Gillies, Michael A.; Cruden, Nicholas L. (Journal of Thoracic Disease; Vol 9, No 5 (May 28, 2017): Journal of Thoracic Disease, 2017)
“Dear colleague, this 68 year old diabetic lady recently underwent percutaneous coronary intervention with drug eluting stents. Unfortunately, she now requires hip replacement surgery. I would be grateful for your advice regarding the optimal timing of surgery …”